1989
DOI: 10.1111/j.1440-1827.1989.tb01508.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Elastic Fibers in Elastosis of Breast Carcinoma UItrastructuraI and ImmunohistochemicaI Studies

Abstract: Elastosis in benign and malignant breast lesions was studied by light microscopic immunohistochemistry for elastin and by electron microscopy. Upon immunohistochemical examination for elastin, elastosis, particularly in scirrhous‐type ductal carcinoma, showed two characteristic staining patterns: fibrously and intensely stained elastic fibers and evenly stained elastic masses. Elastic fibers showing increased fibrous staining occurred mainly in the stromal areas, and were considered to be newly formed because … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…These findings suggest that MPD strictures are not always provoked by destruction or filling with cancer cells. The elastosis observed here resembles the periductal elastosis seen in scirrhous‐type ductal carcinoma of the breast and, 12 while the underlying mechanisms remain unknown, it might be considered part of the desmoplastic stromal reaction to carcinoma cells. In the normal pancreas, myofibroblasts exist mainly in the outer region of the MPD wall where they regulate intraductal pressure 13 but, in this case, no myofibroblasts were found in the wall of the stenotic MPD, whereas fibroblasts had proliferated.…”
Section: Discussionmentioning
confidence: 53%
“…These findings suggest that MPD strictures are not always provoked by destruction or filling with cancer cells. The elastosis observed here resembles the periductal elastosis seen in scirrhous‐type ductal carcinoma of the breast and, 12 while the underlying mechanisms remain unknown, it might be considered part of the desmoplastic stromal reaction to carcinoma cells. In the normal pancreas, myofibroblasts exist mainly in the outer region of the MPD wall where they regulate intraductal pressure 13 but, in this case, no myofibroblasts were found in the wall of the stenotic MPD, whereas fibroblasts had proliferated.…”
Section: Discussionmentioning
confidence: 53%
“…As a component of vasculature and ECM in normal stroma, elastin exhibited changes associated with the neoplastic process. Uchiyama et al identified ‘breast cancer elastosis’ as condensed accumulations of irregularly arranged small amorphous elastin components associated with only a few microfibrils . These amorphous components were ill‐defined and occasionally associated with spiraling collagen fibrils and cellular debris.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12] However, in the breast, not only blood vessels but also mammary ducts are often coated by elastic fibers, and the presence of tumor cells in an elastic ring does not always indicate BVI: it could be a ductal carcinoma in situ (DCIS) component, which is often left within invasive carcinoma. [13][14][15][16] This makes the evaluation of BVI difficult. 17,18 Various criteria, such as focusing just on peritumor areas or lesions in one of paired vessels, have been introduced to avoid mistaking DCIS components as BVI.…”
Section: Introductionmentioning
confidence: 99%